A Missed Opportunity: The Rhetoric of Social Cohesion in Parliamentary Debates - 1994 – 2014 - Rahman, Zarina (Department of Private Law, 2023)
Introduction: This thesis aims to explore whether the parliamentary rhetoric of Members of Parliament as leaders in South Africa contributed to social cohesion in the country. The motivation for the thesis was the violent actions by South Africans towards foreign nationals, specifically from the African and Indian sub-continent, who had migrated to the country in search of better prospects. Based on the country's history of racial discrimination and oppression, the thesis explores whether leaders were conscious of the need to build a South African identity that coheres sufficiently to accept and adjust to such social changes. Method: The thesis analyses parliamentary rhetoric during periods of crisis in the first twenty years of the South African democracy with the aim of ascertaining whether speakers display the ethos required to encourage social cohesion based on values. To delineate the available information into feasible segments, the thesis identified an area of crisis relating to each of the three Presidents during this period: Mandela (Truth and Reconciliation Commission (TRC)), Mbeki (HIV/Aids), and Zuma (Marikana). In addition to a rhetorical analysis, the thesis examines the extent to which speakers display an awareness of their audience(s). Findings: Although the tensions of the apartheid past remained evident during the debates about the Truth and Reconciliation Commission, as it was early in the democracy and the memories of that past was relatively fresh, there was some attempt to build coherence around values. However, the analysis of subsequent debates indicates a stronger adherence by Members of Parliament to party political positions than to the representation of the interests of the public on whose behalf they were debating. While expressing a party position is the norm within functioning established democracies, in the South African context, it tended to ignore the extent of the residual divisions and, consequently the best interests of the nation. The thesis recommends that the citizens of the country use their constitutional rights to rhetorically express their needs and to ensure that their voices are heard.